Development and validation of a general and easy assessable scoring system for laparoscopic skills using a virtual reality simulator. (October 2019) - Goderstad, JM; Sandvik, L; Fosse, E; Lieng, M
Abstract: Objectives: To develop and validate a scoring system for laparoscopic skills for five specific tasks on a virtual reality simulator. Study design: A longitudinal, experimental, non-randomised study including 30 gynecologists and gynecological trainees at three hospitals. The participants were categorized as inexperienced (Group 1), moderately experienced (Group 2), and experienced (Group 3). The study participants performed ten repetitions of three basic skill tasks, a salpingectomy and a laparoscopic supracervical hysterectomy on a virtual reality simulator. Assessment of skills was based on time, error parameters and economy of movements measured by the simulator. We used the results (mean and SD for each parameter in all tasks) of the four last repetitions performed by the experienced gynecologists as the basic for the scoring system. Performance equal to, and higher than, this mean score gave 2 points. A decrease of 1 SD from the mean gave 1 point. Every score below gave 0 points. The mean score for the inexperienced, moderately experienced and experienced study participants was compared. Results: The mean scores in Task 1 were 3.4 (SD 0.6) in Group 1, 3.4 (SD 0.6) in Group 2 and 5.1 (SD 1.1) in Group 3, respectively. There was a statistically significant difference in score between Group 1 and 3 (p = 0.01), and group 2 and 3 (p = 0.01). In Task 2 no statistical significant differences were found. In Task 3, the total mean scores were 1.7 (SD 0.7) in Group 1, 1.9 (SD 0.9) in Group 2 and 2.8 (SD 0.5) in Group 3, respectively. The difference in score between study groups was statistically significant when comparing Group 1 and Group 3 (p < 0.01) and Group 2 and Group 3 (p = 0.02). In Task 4, the difference in used time between group 1 and 3 was statistically significant (p = 0.03). In task 5 there was a significant difference in performance score between group 1 and 3 (p = 0.01). Conclusions: There was significant difference in scores between the experienced and the inexperienced gynecologist in four out of five tasks. The scoring system is easy assessable and can be used for summative and formative feedback in proficiency-based assessment.